Vicagrel is hydrolyzed by Raf kinase inhibitor protein in human intestine. (23rd December 2022) - Zhu, Ting; Wu, Yu; Li, Xue‐Mei; Jia, Yu‐Meng; Zhou, Huan; Jiang, Li‐Ping; Tai, Ting; Mi, Qiong‐Yu; Ji, Jin‐Zi; Xie, Hong‐Guang
Abstract: As an analog of clopidogrel and prasugrel, vicagrel is completely hydrolyzed to intermediate thiolactone metabolite 2‐oxo‐clopidogrel (also the precursor of active thiol metabolite H4) in human intestine, predominantly by AADAC and CES2; however, other unknown vicagrel hydrolases remain to be identified. In this study, recombinant human Raf kinase inhibitor protein (rhRKIP) and pooled human intestinal S9 (HIS9) fractions and microsome (HIM) preparations were used as the different enzyme sources; prasugrel as a probe drug for RKIP (a positive control), vicagrel as a substrate drug of interest, and the rate of the formation of thiolactone metabolites 2‐oxo‐clopidogrel and R95913 as metrics of hydrolase activity examined, respectively. In addition, an IC50 value of inhibition of rhRKIP‐catalyzed vicagrel hydrolysis by locostatin was measured, and five classical esterase inhibitors with distinct esterase selectivity were used to dissect the involvement of multiple hydrolases in vicagrel hydrolysis. The results showed that rhRKIP hydrolyzed vicagrel in vitro, with the values of Km, Vmax, and CLint measured as 20.04 ± 1.99 μM, 434.60 ± 12.46 nM/min/mg protein, and 21.69 ± 0.28 ml/min/mg protein, respectively, and that an IC50 value of locostatin was estimated as 1.24 ± 0.04 mM for rhRKIP. In addition to locostatin, eserine and vinblastine strongly suppressed vicagrel hydrolysis in HIM. It is concluded that RKIP can catalyze the hydrolysis of vicagrel in the human intestine, and that vicagrel can be hydrolyzed by multiple hydrolases, such as RKIP, AADAC, and CES2, concomitantly. Abstract : As a promising novel antiplatelet drug and an analog of clopidogrel and prasugrel, vicagrel is hydrolyzed to its thiolactone metabolite 2‐oxo‐clopidogrel by esterases AADAC and CES2 in human intestine. In this study, vicagrel was hydrolyzed to 2‐oxo‐clopidogrel by RKIP (Raf kinase inhibitor protein) as measured with recombinant human RKIP and human intestine S9 and microsome preparations, respectively, showing that vicagrel is the second substrate drug of RKIP in humans, next to prasugrel.